The role of grit and self-efficacy in teacher engagement and burnout - Lailla, Nor; Rao, Don Gusti; Hakim, Luqman; Nugroho, Wawan Sadtyo (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to examine the influence of grit and self-efficacy on work engagement, to identify the relationship between grit and self-efficacy, and to determine how work engagement affects burnout. Research Methodology: This uses a quantitative approach with a type of study. Population in the study: This is a vocational school teacher in seven schools in Jakarta, Bogor, Tangerang, Depok, and South Tangerang. The sample was determined using non-probability sampling techniques, especially convenience sampling. The number of respondents is as many as 107. Data collection techniques use Google Forms. Data analysis techniques using SmartPLS. Results: The results show a positive influence of grit on work engagement, a positive influence of self-efficacy on work engagement, a positive relationship between grit and self-efficacy, and a negative influence of work engagement on burnout. Conclusions: This study concludes that grit and self-efficacy positively influence work engagement, with teachers displaying greater emotional, cognitive, and physical involvement in their work. Grit also enhances self-efficacy, which strengthens engagement, ultimately reducing burnout. These findings emphasize the importance of fostering perseverance and confidence to improve workplace health and productivity in education. Limitations: This study discusses the variables of grit, self-efficacy, work engagement, and burnout. However, there are still many other factors that influence teacher engagement and work burnout, such as principal leadership, organizational support for work-life balance, or other external factors. Contribution: This research suggests that grit and self-efficacy have an important role in work engagement and reducing burnout in teachers, as well as being the basis for developing teacher welfare, especially in Indonesia.